(untitled) (Neliniini Kolyvannya, 2025)
We investigate the two-point boundary-value-problem for the singularly perturbed differential-algebraic system in the case of simple roots of the characteristic equation. We determine the sufficient conditions for the existence and uniqueness of the solution of this boundary-value problem and give its asymptotic expansion.